Analisis Pengolahan Sampah Pada Tempat Pengolahan Sampah Terpadu (TPST) Selopuro Kabupaten Ngawi - Kurnia Sari, Hanna Putri; Rosariawari, Firra; Maroeto; Krisnawati, Anik (Jurnal Serambi Engineering, 2025)
Waste is the residual result of daily human activity that is no longer wanted and that needs to go through a good treatment process so that it does not cause problems for the environment. The increase in waste generation is due to the high consumption of people and the increase in population growth. The increase in the amount of waste generation will certainly lead to an increase in the amount of waste entering the final processing site or landfill and will affect the life of the landfill itself. Therefore, the construction of the TPST is a solution to reduce the amount of waste going to the landfill and increase the amount of integrated waste processing in Ngawi Regency. This study aims to analyse the waste processing process at TPST Selopuro, Ngawi Regency and to see the results of the waste processing process at TPST Selopuro and the waste processing methods applied at TPST Selopuro. The data collection method includes primary and secondary data, and the results include data on incoming waste generation and data on the results of the waste processing process at the integrated waste management site.